Pathophysiology, Clinical Characteristics of Diabetic Cardiomyopathy: Therapeutic Potential of Natural Polyphenols - Atale, Neha; Yadav, Dhananjay; Rani, Vibha; Jin, Jun-O (Frontiers in Nutrition, 2020)
Diabetic cardiomyopathy (DCM) is an outcome of disturbances in metabolic activities through oxidative stress, local inflammation, and fibrosis, as well as a prime cause of fatality worldwide. Cardiovascular disorders in diabetic individuals have become a challenge in the diagnosis and formulation of treatment prototype. It is necessary to have a better understanding of cellular pathophysiology that reveal the therapeutic targets and prevent the progression of cardiovascular diseases due to hyperglycemia. Critical changes in levels of collagen and integrin have been observed in the extracellular matrix of heart, which was responsible for cardiac remodeling in diabetic patients. This review explored the understanding of the mechanisms of how the phytochemicals provide cardioprotection under diabetes along with the caveats and provide future perspectives on these agents as prototypes for the development of drugs for managing DCM. Thus, here we summarized the effect of various plant extracts and natural polyphenols tested in preclinical and cell culture models of diabetic cardiomyopathy. Further, the potential use of selected polyphenols that improved the therapeutic efficacy against diabetic cardiomyopathy is also illustrated.